Oral Administration of Recombinant Saccharomyces boulardii Expressing Ovalbumin-CPE Fusion Protein Induces Antibody Response in Mice - Bagherpour, Ghasem; Ghasemi, Hosnie; Zand, Bahare; Zarei, Najmeh; Roohvand, Farzin; Ardakani, Esmat M.; Azizi, Mohammad; Khalaj, Vahid (Frontiers in Microbiology, 2018)
Saccharomyces boulardii, a subspecies of Saccharomyces cerevisiae, is a well-known eukaryotic probiotic with many benefits for human health. In the present study, a recombinant strain of S. boulardii was prepared to use as a potential oral vaccine delivery vehicle. In this sense, a ura3 auxotroph strain of S. boulardii CNCM I-745 (known as Saccharomyces cerevisiae HANSEN CBS 5926, Yomogi®) was generated using CRISPR/Cas9 methodology. Then a gene construct encoding a highly immunogenic protein, ovalbumin (OVA), was prepared and transformed into the ura3- S. boulardii. To facilitate the transport of the recombinant immunogen across the intestinal barrier, a claudin- targeting sequence from Clostridium perfringens enterotoxin (CPE) was added to the C-terminus of the expression cassette. The recombinant S. boulardii strain expressing the OVA-CPE fusion protein was then administered orally to a group of mice, and serum IgG and fecal IgA levels were evaluated by ELISA. Our results demonstrated that anti-OVA IgG in serum significantly increased in test group (P < 0.001) compared to control groups (receiving wild type S. boulardii or PBS), and the fecal IgA titer was significantly higher in test group (p < 0.05) than control groups. In parallel, a recombinant S. boulardii strain expressing the similar construct lacking C-terminal CPE was also administered orally. The result showed an increased level of serum IgG in group receiving yeasts expressing the CPE negative construct compared to control groups (P < 0.05); however, the fecal IgA levels did not increase significantly. In conclusion, our findings indicated that the yeast S. boulardii, as a delivery vehicle with possible immunomodulatory effects, and c-CPE, as a targeting tag, synergistically assist to stimulate systemic and local immunity. This proposed recombinant S. boulardii system might be useful in the expression of other antigenic peptides, making it as a promising tool for oral delivery of vaccines or therapeutic proteins.